The Implementation of Role Play-Learning Model to Enhance Understanding and Speaking Skills in English Among 11th-Grade Students at Ma Swasta Hubbulwathan Duri (LPPM STMIK Dharmapala Riau, 2023)
Children prefer to communicate in Indonesian rather than English at home and at school, which is a challenge teachers face when teaching English. This research aims to help students of class XI at Hubbulwathan Duri Private MA overcome the challenges of learning English, specifically to improve their understanding of role-playing. The quantitative method that the authors use in this study considers the facts determining how to evaluate students for role-playing lessons in class. According to research findings, role-playing in class can motivate students to participate in their education actively. Applying the role-play learning model can improve students' English speaking skills by up to 20% and succeed with learning mastery reaching 75%. Furthermore, it can be concluded that applying the role-play learning achievement model can minimize students' speaking errors.